Metastatic seminoma in a Male alpine goat: Clinical and histopathological approach - Cosentino, Isabel Oliveira; Balaro, Mario Felipe Alvarez; da Silva Carvalho, Ana Beatriz; Trevizan, Juliane Teramachi [UNESP]; Brandão, Felipe Zandonadi; Fava, Claudia Del (Universidade Federal do Rio Grande do Sul, 2019)
Background: Seminomas are germ cell tumors mainly originating from spermatogonia in the seminiferous tubules and has been described in several domestic animal species, even though has rarely been described in goats. Moreover, seminomas tumors are not usually metastatic and rarely trigger paraneoplastic syndrome. In this sense, this is a case report of a 12-year-old male Alpine goat, suspected of testicular neoplasm based on clinical examination and ultrasound imaging, diagnosed as a seminoma with metastasis in liver by histopathology upon necropsy. Case: A 12-year-old male Alpine goat presented a 10 month history of progressive weight loss, prostration, and scrotal sac enlargement. The major clinical findings were pale conjunctival mucus, bilateral nasal catarrhal secretion, obstructive dyspnea, an increased abdominal component, crackling at trachea auscultation, silence upon lung auscultation of the ventral area and wheezing upon auscultation of the dorsal area, and enlargement of the left testicle with contralateral atrophy. At the Ultrasonography scan, the enlarged left testicle presented architecture loss, as well as circumscribed masses differing in echogenicity and echotexture with scattered small hyperechoic nodules. The shrunken right testicle showed acoustic shading across the surface suggestive of calcification. Due to the poor prognosis and regard for animal welfare, the goat was euthanized. The main necropsy findings on testicles were: enlarged left testicle with white parenchyma on the dorsal side as well as diffuse yellow elliptical lesions of 0.5-2.5 cm on the surface in association with two circumscribed areas at the cranial and caudal poles, firm upon cutting. The right testicle was half the typical size, slightly pale, firm at cutting of the tunica albuginea, and presented dark parenchyma with abundant calcification dots suggestive of microlithiasis. The histological findings included diffuse tumoral stroma of the left testicle composed of large, polyhedral, discretely demarcated circular cells exhibiting a large nucleus varying in size with little cytoplasm and a high mitotic rate. The right testicle exhibited areas of necrosis and fibrosis of the testicular parenchyma, contiguous with the area of degeneration and normal parenchyma, caseous necrosis, and focal calcification. The liver presented some foci of the same cellular pattern of the seminoma, as described in the parenchyma. The findings summarized at necropsy and histopathological evaluation were seminoma in the left testicle, with metastasis to the liver; degeneration and necrosis of the right testicle with abscess and calcification. Discussion: Seminoma has been described in several species, even though rarely in goats. This report was the second ever seminoma reported in caprine species, and particularly this case presented liver metastasis, showing the pathologic potential of this neoplasia for this species, and it differed from first reported which described ulcerative lesions in, and adhesion of the skin covering the testis. Regarding the US scan, even though this technique cannot be considered as a conclusive diagnostic, it may help to reach a prognosis by the tumor's characteristics. An US scan along with cytology or biopsy enables an earlier diagnosis of testicular lesions and prognosis. Orchidectomy, when unilateral, can be carried out to increase the animal's productive life.
Keywords: Capra hircus; Neoplasia; Testis; Ultrasonography